Analisis Kelayakan Usaha ditinjau dari Aspek Pemasaran (Studi Kasus pada Warung Bakso Bagus Kecamatan Rappocini) - Sitti Hajerah Hasyim (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
This study aims to find out how the feasibility of the Bakso Bagus stall business is seen in terms of market and marketing aspects. The type of research used is qualitative research, where data is obtained directly in the field through surveys and interviews. As for the informants in this study, there were 3 people consisting of Bakso Bagus stall owners, employees and consumers. The data analysis used is descriptive analysis from the results of interviews related to business feasibility from the marketing aspect which consists of product, price, place, promotion, people, physical evidence and process. The results of the study show that Bakso Bagus implements alternative strategies in terms of market and marketing so that it can be said that Bakso Bagus is feasible to develop.